Positive electrode active material for secondary battery, positive electrode for secondary battery, and secondary battery

By using layered rock salt-type lithium composite oxides in secondary batteries and ensuring their chemical structural characteristics through specific analytical methods, the problem of insufficient performance of existing secondary batteries is solved, and excellent primary capacity, cycle stability and storage characteristics are achieved.

CN116157884BActive Publication Date: 2025-03-11MURATA MFG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180059448.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-27
Filing Date
2021-03-10
Publication Date
2025-03-11
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

There is still room for improvement in the existing secondary batteries in terms of primary capacity characteristics, cycle characteristics and storage characteristics, and it is difficult to achieve excellent performance.

Method used

Laminated rock salt type lithium composite oxide is used as the positive electrode active substance. The composite oxide includes lithium, cobalt, aluminum, magnesium, additional elements (such as fluorine, phosphorus, sulfur) and oxygen. Through inductively coupled plasma emission spectroscopy analysis method and X-ray photoelectron energy spectroscopy and other analytical methods, the aluminum content is greater than that of magnesium, and the chemical bond state of magnesium and oxygen and additional elements is better than that of aluminum and oxygen and additional elements.

Benefits of technology

The excellent primary capacity, cycle characteristics and storage characteristics of the secondary battery are realized, and the overall performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116157884B_ABST
    Figure CN116157884B_ABST
Patent Text Reader

Abstract

The secondary battery comprises a positive electrode, a negative electrode and an electrolyte containing a positive electrode active material. The positive electrode active material comprises a layered rock salt type lithium composite oxide, the lithium composite oxide comprises lithium, cobalt, aluminum, magnesium, an additional element, and oxygen as constituent elements, and the additional element comprises at least one of fluorine, phosphorus and sulfur. When the positive electrode active material is analyzed using inductively coupled plasma emission spectrometry, the aluminum content is greater than the magnesium content, and when the surface of the positive electrode active material is analyzed using X-ray photoelectron spectroscopy, the sum of the amount of the chemical bond state of magnesium and oxygen and the amount of the chemical bond state of magnesium and the additional element is greater than the sum of the amount of the chemical bond state of aluminum and oxygen and the amount of the chemical bond state of aluminum and the additional element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present technology relates to a positive electrode active material for a secondary battery, a positive electrode for a secondary battery, and a secondary battery. Background Art

[0002] As various electronic devices such as mobile phones are becoming popular, secondary batteries are being developed as small, lightweight power sources that can also obtain high energy density. The secondary battery has a positive electrode (positive electrode for secondary batteries), a negative electrode, and an electrolyte, and the positive electrode contains a positive electrode active material (positive electrode active material for secondary batteries) that participates in the charge and discharge reaction.

[0003] Various studies have been conducted on the structure of secondary batteries. Specifically, in order to suppress the dissolution of cobalt from the positive electrode active material, elements such as zirconium and fluorine are attached to the surface of the lithium transition metal oxide containing cobalt (for example, refer to patent document 1.). In order to suppress the reduction of capacity during charge and discharge, a positive electrode active material having lithium, transition metal and oxygen in the first region (inside) and magnesium, fluorine and oxygen in the second region (surface part and part of the inside) is used (for example, refer to patent document 2.). In order to obtain excellent charge and discharge cycle durability, etc., a mixture of lithium raw material compounds, N element raw material compounds such as cobalt, M element raw material compounds such as aluminum, L element raw material compounds such as phosphorus, and fluorine raw material compounds is calcined in an oxygen-containing atmosphere to manufacture a lithium-containing composite oxide (for example, refer to patent document 3.).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-507343

[0007] Patent Document 2: Japanese Patent Application Publication No. 2018-190700

[0008] Patent Document 3: Japanese Patent Application Publication No. 2005-347211 Summary of the invention

[0009] Various studies have been conducted to improve the performance of secondary batteries, but the initial capacity characteristics, cycle characteristics, and storage characteristics of the secondary batteries are still insufficient, and thus there is room for improvement.

[0010] The present technology has been made in view of the above-mentioned problems, and an object of the present invention is to provide a positive electrode active material for a secondary battery, a positive electrode for a secondary battery, and a secondary battery that can obtain excellent initial capacity characteristics, cycle characteristics, and storage characteristics.

[0011] A positive electrode active material for a secondary battery according to an embodiment of the present technology includes a layered rock salt type lithium composite oxide, the lithium composite oxide includes lithium, cobalt, aluminum, magnesium, an additional element, and oxygen as constituent elements, the additional element including at least one of fluorine, phosphorus, and sulfur. When analyzed using inductively coupled plasma emission spectrometry, the aluminum content is greater than the magnesium content, and when the surface is analyzed using X-ray photoelectron spectroscopy, the sum of the amount of the chemical bond state of magnesium and oxygen and the amount of the chemical bond state of magnesium and the additional element is greater than the sum of the amount of the chemical bond state of aluminum and oxygen and the amount of the chemical bond state of aluminum and the additional element.

[0012] A positive electrode for a secondary battery according to an embodiment of the present technology includes a positive electrode active material having the same structure as that of the positive electrode active material for a secondary battery according to an embodiment of the present technology described above.

[0013] A secondary battery according to an embodiment of the present technology includes a positive electrode, a negative electrode, and an electrolyte solution. The positive electrode has the same structure as the positive electrode for a secondary battery according to the embodiment of the present technology described above.

[0014] As described above, the content of aluminum and the content of magnesium are determined by the analysis of the positive electrode active material using inductively coupled plasma emission spectrometry. In addition, as described above, the amount of the chemical bond state of magnesium and oxygen, the amount of the chemical bond state of magnesium and the additional element, the amount of the chemical bond state of aluminum and oxygen, and the amount of the chemical bond state of aluminum and the additional element are determined by the surface analysis of the positive electrode active material using X-ray photoelectron spectroscopy. It should be noted that the details of the analysis steps using inductively coupled plasma emission spectrometry and X-ray photoelectron spectroscopy, respectively, will be described later.

[0015] According to a secondary battery positive electrode active material, a secondary battery positive electrode or a secondary battery of one embodiment of the present technology, the positive electrode active material (layered rock salt type lithium composite oxide) contains lithium, cobalt, aluminum, magnesium, additional elements and oxygen as constituent elements. In addition, the analysis results of the positive electrode active material using inductively coupled plasma emission spectrometry meet the above conditions, and the analysis results of the surface of the positive electrode active material using X-ray photoelectron spectroscopy meet the above conditions. Therefore, excellent initial capacity characteristics, cycle characteristics and storage characteristics can be obtained.

[0016] It should be noted that the effects of the present technology are not necessarily limited to the effects described here, and may be any of a series of effects related to the present technology described later. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1It is a perspective view showing the structure of a secondary battery in one embodiment of the present technology.

[0018] Figure 2 Yes means Figure 1 A cross-sectional view of the structure of a battery element is shown.

[0019] Figure 3 It is a block diagram showing the structure of an application example of a secondary battery.

[0020] Figure 4 It is a cross-sectional view showing the structure of a secondary battery used for testing. DETAILED DESCRIPTION

[0021] Hereinafter, one embodiment of the present technology will be described in detail with reference to the drawings. It should be noted that the order of description is as follows.

[0022] 1. Secondary battery (positive electrode active material for secondary battery and positive electrode for secondary battery)

[0023] 1-1. Structure

[0024] 1-2.Physical properties

[0025] 1-3. Action

[0026] 1-4. Manufacturing method

[0027] 1-5. Function and effect

[0028] 2. Modifications

[0029] 3. Uses of secondary batteries

[0030] <1. Secondary battery (positive electrode active material for secondary battery and positive electrode for secondary battery)>

[0031] First, a secondary battery according to an embodiment of the present technology is described. It should be noted that a positive electrode active material for a secondary battery according to an embodiment of the present technology (hereinafter referred to as "positive electrode active material") and a positive electrode for a secondary battery according to an embodiment of the present technology (hereinafter referred to as "positive electrode") are each a part (a constituent element) of the secondary battery, so these positive electrode active materials and positive electrodes are described together below.

[0032] The secondary battery described herein is a secondary battery that obtains battery capacity by embedding and de-embedding electrode reaction substances, and it has a positive electrode, a negative electrode, and a liquid electrolyte, i.e., an electrolyte. In this secondary battery, in order to prevent the electrode reaction substances from precipitating on the surface of the negative electrode during charging, the charge capacity of the negative electrode becomes greater than the discharge capacity of the positive electrode. That is, the electrochemical capacity per unit area of ​​the negative electrode is set to become greater than the electrochemical capacity per unit area of ​​the positive electrode.

[0033] The type of electrode reaction material is not particularly limited, and specifically, it is a light metal such as an alkali metal and an alkaline earth metal. The alkali metals are lithium, sodium, and potassium, and the alkaline earth metals are beryllium, magnesium, and calcium.

[0034] Hereinafter, the case where the electrode reaction material is lithium is taken as an example. A secondary battery that obtains battery capacity by inserting and extracting lithium is a so-called lithium ion secondary battery. In this lithium ion secondary battery, lithium is inserted and extracted in an ionic state.

[0035] <1-1. Structure>

[0036] Figure 1 The three-dimensional structure of the secondary battery is shown. Figure 2 Shows Figure 1 The cross-sectional structure of the battery element 20 shown. Figure 1 The outer packaging film 10 and the battery element 20 are shown in a state where they are separated from each other. Figure 2 Only a portion of the battery element 20 is shown.

[0037] like Figure 1 as well as Figure 2 As shown, the secondary battery comprises an outer packaging film 10, a battery element 20, a positive electrode lead 31 and a negative electrode lead 32, and sealing films 41 and 42. The secondary battery described here is a laminated film type secondary battery using a flexible (or pliable) outer packaging member (outer packaging film 10) as an outer packaging member for accommodating the battery element 20.

[0038] [Outer packaging film]

[0039] like Figure 1 As shown, the outer film 10 is a flexible outer packaging member that accommodates the battery element 20, that is, the positive electrode 21, the negative electrode 22 and the electrolyte solution described later, and has a bag-like structure.

[0040] Here, the outer film 10 is a single film-shaped member that can be folded along the folding direction R. The outer film 10 is provided with a recessed portion 10U (so-called deep-drawn portion) for accommodating the battery element 20 .

[0041] The structure (material, number of layers, etc.) of the outer film 10 is not particularly limited. Therefore, the outer film 10 may be a single-layer film or a multi-layer film.

[0042] Here, the outer packaging film 10 is a three-layer laminated film in which a welding layer, a metal layer, and a surface protection layer are stacked in sequence from the inside. The welding layer contains a polymer compound such as polypropylene. The metal layer contains a metal material such as aluminum. The surface protection layer contains a polymer compound such as nylon. When the outer packaging film 10 is folded, the outer peripheral edges of the outer packaging films 10 (welding layers) facing each other are welded to each other.

[0043] [Sealing film]

[0044] like Figure 1 As shown, the sealing films 41 and 42 are sealing members for preventing external air and the like from intruding into the interior of the outer film 10. The sealing film 41 is inserted between the outer film 10 and the positive electrode lead 31, and the sealing film 42 is inserted between the outer film 10 and the negative electrode lead 32. In addition, one or both of the sealing films 41 and 42 may be omitted.

[0045] Specifically, the sealing film 41 is made of a polymer compound such as polyolefin having adhesion to the positive electrode lead 31 , and the polyolefin is polypropylene or the like.

[0046] The structure of the sealing film 42 is the same as that of the sealing film 41 except that the sealing film 42 has close adhesion to the negative electrode lead 32. That is, the sealing film 42 contains a polymer compound such as polyolefin that has close adhesion to the negative electrode lead 32.

[0047] [Battery components]

[0048] like Figure 1 as well as Figure 2 As shown, the battery element 20 is a power generation element housed in the outer film 10 , and includes a positive electrode 21 , a negative electrode 22 , a separator 23 , and an electrolyte (not shown).

[0049] Here, the battery element 20 is a so-called wound electrode body. That is, in the battery element 20, the positive electrode 21 and the negative electrode 22 are stacked on each other with the separator 23 interposed therebetween, and the positive electrode 21, the negative electrode 22 and the separator 23 are wound around the winding axis (the imaginary axis extending along the Y-axis direction). Therefore, the positive electrode 21 and the negative electrode 22 are wound so as to face each other with the separator 23 interposed therebetween.

[0050] Since the battery element 20 has a flat three-dimensional shape, the shape of the cross section of the battery element 20 intersecting the winding axis (the cross section along the XZ plane) is a flat shape defined by a major axis and a minor axis. The major axis is an imaginary axis extending in the X-axis direction and having a greater length than the minor axis, and the minor axis is an imaginary axis extending in the Z-axis direction intersecting the X-axis direction and having a smaller length than the major axis. Here, the cross-sectional shape of the battery element 20 is a flat, substantially elliptical shape.

[0051] (positive electrode)

[0052] The positive electrode 21 is a positive electrode for a secondary battery according to an embodiment of the present technology, such as Figure 2 As shown, the positive electrode 21 includes a positive electrode current collector 21A and a positive electrode active material layer 21B. As described later, the positive electrode 21 includes a positive electrode active material that participates in charge and discharge reactions.

[0053] The positive electrode current collector 21A has a pair of surfaces on which the positive electrode active material layer 21B is disposed. The positive electrode current collector 21A is made of a conductive material such as a metal material, and the metal material is aluminum or the like.

[0054] The positive electrode active material layer 21B contains a positive electrode active material for a secondary battery of one embodiment of the present technology, that is, a positive electrode active material, which can insert and extract lithium. Here, the positive electrode active material layer 21B is provided on both sides of the positive electrode collector 21A. In addition, the positive electrode active material layer 21B may further include a positive electrode binder and a positive electrode conductor, etc. In addition, the positive electrode active material layer 21B may be provided only on a single side of the positive electrode collector 21A. The formation method of the positive electrode active material layer 21B is not particularly limited, and specifically, it is a coating method, etc.

[0055] The positive electrode active material includes any one or more of layered rock salt type lithium composite oxides. That is, the lithium composite oxide has a layered rock salt type crystal structure. Specifically, the lithium composite oxide includes lithium, cobalt, aluminum, magnesium, additional elements and oxygen as constituent elements, and the additional elements include any one or more of fluorine, phosphorus and sulfur. This is because high energy density can be obtained.

[0056] As described above, the composition of the lithium composite oxide is not particularly limited, as long as the lithium composite oxide has a layered rock salt type crystal structure and contains a series of constituent elements such as lithium. Among them, the molar ratio of cobalt is preferably greater than the molar ratio of each of aluminum, magnesium and additional elements. That is, the lithium composite oxide preferably contains cobalt as the main component (main constituent element) among the constituent elements (cobalt, aluminum, magnesium and additional elements) other than lithium and oxygen. This is because a higher energy density can be obtained.

[0057] Specifically, the lithium composite oxide preferably includes a compound represented by the following formula (1): X in the formula (1) is the above-mentioned additional element.

[0058] Li a Co b Al c Mg d X e O f …(1)

[0059] (X is any one or more of F, P and S. a, b, c, d, e and f satisfy 0.90≤a≤1.10, 0.80≤b≤0.98, 0.001≤c≤0.3, 0.001≤d≤0.3, 0≤e≤0.3 and 1.8≤f≤2.1.)

[0060] Here, in order to improve the performance of the secondary battery, the physical properties of the positive electrode active material (lithium composite oxide) must satisfy predetermined conditions (physical property conditions). The details of the physical property conditions will be described later.

[0061] It should be noted that, in addition to the above-mentioned lithium composite oxides, the positive electrode active material may further contain any one or two or more of the lithium compounds. In addition, the lithium composite oxides already described are not included in the lithium compounds described here.

[0062] The lithium compound is a general term for compounds containing lithium as a constituent element, more specifically, a compound containing lithium and one or more transition metal elements as constituent elements. In addition, the lithium compound may further contain any one or more of other elements (elements other than lithium and transition metal elements). The type of lithium compound is not particularly limited, specifically, oxides, phosphate compounds, silicate compounds and boric acid compounds. Specific examples of oxides are LiNiO2, LiCoO2 and LiMn2O4, etc., and specific examples of phosphate compounds are LiFePO4 and LiMnPO4, etc.

[0063] The positive electrode binder includes any one or more of synthetic rubber and polymer compounds. The synthetic rubber is styrene-butadiene rubber, etc., and the polymer compound is polyvinylidene fluoride, etc. The positive electrode conductor includes conductive materials such as carbon materials, and the carbon material is graphite, carbon black, acetylene black, and Ketjen black, etc. In addition, the conductive material can also be a metal material and a polymer compound, etc.

[0064] (negative electrode)

[0065] like Figure 2 As shown, the negative electrode 22 includes a negative electrode current collector 22A and a negative electrode active material layer 22B.

[0066] The negative electrode current collector 22A has a pair of surfaces on which the negative electrode active material layer 22B is disposed. The negative electrode current collector 22A is made of a conductive material such as a metal material, and the metal material is copper or the like.

[0067] The negative electrode active material layer 22B contains any one or more of the negative electrode active materials capable of inserting and extracting lithium, and here, the negative electrode active material layer 22B is arranged on both sides of the negative electrode collector 22A. In addition, the negative electrode active material layer 22B may also contain a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material layer 22B may be arranged only on a single side of the negative electrode collector 22A. The details of the negative electrode binder and the negative electrode conductive agent are the same as the details of the positive electrode binder and the positive electrode conductive agent. The method for forming the negative electrode active material layer 22B is not particularly limited, and specifically, it is any one or more of a coating method, a gas phase method, a liquid phase method, a spraying method, and a sintering method (sintering method).

[0068] The negative electrode active material is a carbon material and a metal material. This is because a high energy density can be obtained. The carbon material is graphitizable carbon, non-graphitizable carbon, and graphite (natural graphite and artificial graphite). The metal material is a general term for materials containing any one or two or more of the metal elements and semi-metal elements that can form an alloy with lithium as constituent elements. The metal element and semi-metal element are silicon and tin. The metal material can be a monomer, an alloy, a compound, a mixture of two or more thereof, or a material containing two or more phases thereof. Specific examples of metal materials are TiSi2 and SiO x (0<x≤2, or 0.2<x<1.4) etc.

[0069] (Diaphragm)

[0070] like Figure 2 As shown, the separator 23 is an insulating porous film interposed between the positive electrode 21 and the negative electrode 22, and allows lithium ions to pass therethrough while preventing contact (short circuit) between the positive electrode 21 and the negative electrode 22. The separator 23 is made of a polymer compound such as polyethylene.

[0071] (Electrolyte)

[0072] The electrolytic solution is impregnated in each of the positive electrode 21 , the negative electrode 22 , and the separator 23 , and contains a solvent and an electrolyte salt.

[0073] The solvent includes any one or more of non-aqueous solvents (organic solvents) such as carbonate compounds, carboxylate compounds, and lactone compounds, and the electrolyte solution including the non-aqueous solvent is a so-called non-aqueous electrolyte solution. The electrolyte salt includes any one or more of light metal salts such as lithium salts.

[0074] [Positive lead and negative lead]

[0075] like Figure 1As shown, the positive electrode lead 31 is a positive electrode terminal connected to the battery element 20 (positive electrode 21), and is led out from the inside of the outer film 10. The positive electrode lead 31 includes a conductive material such as aluminum, and the shape of the positive electrode lead 31 is any one of a thin plate and a mesh.

[0076] like Figure 1 As shown, the negative electrode lead 32 is a negative electrode terminal connected to the battery element 20 (negative electrode 22), and is led out from the inside of the outer film 10 to the outside in the same direction as the leading direction of the positive electrode lead 31. The negative electrode lead 32 is made of a conductive material such as copper, and the details of the shape of the negative electrode lead 32 are the same as those of the positive electrode lead 31.

[0077] <1-2. Physical properties>

[0078] In order to improve the performance (initial capacity characteristics, cycle characteristics, and storage characteristics) of the secondary battery, the physical properties of the positive electrode active material (lithium composite oxide) must satisfy predetermined physical property conditions as described above.

[0079] [Physical properties]

[0080] Specifically, the analysis results (physical properties) of the positive electrode active material (lithium composite oxide) using two analysis methods simultaneously meet the two conditions (physical property conditions 1 and 2) described below. This is because, during charging, while the crystal structure of the positive electrode active material (lithium composite oxide) is stabilized, the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material can be suppressed, so each of the initial capacity characteristics, cycle characteristics, and storage characteristics is improved. It should be noted that the details of the reasons for simultaneously meeting physical property conditions 1 and 2 will be described later.

[0081] (Physical property condition 1)

[0082] When the positive electrode active material was analyzed using an inductively coupled plasma (ICP) emission spectrometry method, the aluminum content CA (ppm) was greater than the magnesium content CM (ppm).

[0083] That is, by analyzing the entire positive electrode active material using ICP emission spectrometry, the aluminum content CA contained in the positive electrode active material and the magnesium content CM contained in the positive electrode active material are measured, and the content CA is greater than the content CM.

[0084] Therefore, in the entire positive electrode active material, when the aluminum content CA and the magnesium content CM are compared with each other, the content CA is larger than the content CM.

[0085] Here, the procedure for measuring the contents CA and CM respectively using ICP emission spectrometry is as follows.

[0086] First, 0.1 g of the positive electrode active material was placed in a 15 ml (15 cm 3 ) in hydrochloric acid (concentration = 1 mol / kg), and then boil the hydrochloric acid. Thus, the positive electrode active material is dissolved in the hydrochloric acid to obtain a dissolved product of the positive electrode active material. Next, the dissolved product of the positive electrode active material is evaporated to dryness to obtain a sample for analysis. Next, the sample is diluted to 100 ml (= 100 cm) using hydrochloric acid (concentration = 0.1 mol / kg). 3 ), thereby preparing a sample solution.

[0087] Next, the sample solution is analyzed using an ICP emission spectrometer to measure the concentration of aluminum and magnesium contained in the sample solution. As the ICP emission spectrometer, an ICP emission spectrometer (sequential type) SPS3100 manufactured by HITACHI HI-TECH SCIENCE CO., LTD. can be used.

[0088] Finally, the aluminum content CA contained in the lithium composite oxide was calculated based on the calculation formula of content CA (ppm) = weight of aluminum / weight of positive electrode active material. In addition, the magnesium content CM contained in the lithium composite oxide was calculated based on the calculation formula of content CM (ppm) = weight of magnesium / weight of positive electrode active material.

[0089] (Physical property condition 2)

[0090] As shown in formula (1), the additional element is set to X. Therefore, when the surface of the positive electrode active material is analyzed using X-ray Photoelectron Spectroscopy (XPS) , the sum PM of the amount of magnesium and oxygen in a chemical bond state (Mg-O) PMO and the amount of magnesium and the additional element in a chemical bond state (Mg-X) PMX is greater than the sum PA of the amount of aluminum and oxygen in a chemical bond state (Al-O) PAO and the amount of aluminum and the additional element in a chemical bond state (Al-X) PAX.

[0091] That is, by using XPS to analyze a part (surface) of the positive electrode active material, the amounts of PMO, PMX, PAO, and PAX are measured respectively, and the sum PM of the amounts of PMO and PMX and the sum PA of the amounts of PAO and PAX are calculated, and the sum PM is greater than the sum PA.

[0092] Thus, in the whole of the positive electrode active material, as described above, the amount of aluminum present (content CA) is greater than the amount of magnesium present (content CM), but in a part (surface) of the positive electrode active material, as described above, the sum PM is greater than the sum PA, so the amount of magnesium present is greater than the amount of aluminum present. That is, in the positive electrode active material, magnesium is biased near the surface.

[0093] Here, the procedure for measuring the amounts of PMO, PMX, PAO, and PAX respectively using XPS is as follows.

[0094] By using an XPS analysis device to analyze (element analysis) the surface of the positive electrode active material, the analysis results (X-ray photoelectron spectroscopy) of all elements contained in the lithium composite oxide are obtained. In this case, as an XPS analysis device, a scanning XPS device Quantera SXM manufactured by ULVAC-PHI Co., Ltd. can be used. In addition, the analysis conditions are: X-ray source = monochromatized Al-Kα (1486.6 eV), X-ray spot diameter = 100 μm. In the X-ray photoelectron spectroscopy, the horizontal axis represents the bond energy (eV) and the vertical axis represents the spectral intensity (the number of X-ray photoelectrons).

[0095] Thereafter, the surface atomic concentration of each element was calculated based on the X-ray photoelectron spectroscopy spectrum (peak area of ​​the number of photoelectrons associated with each element) using a relative sensitivity factor manufactured by ULVAC-PHI Co., Ltd., thereby calculating the amount of PMO, PMX, PAO, and PAX, respectively. In this case, fitting (so-called peak fitting) processing was performed using analysis software (multi pak) manufactured by ULVAC-PHI Co., Ltd.

[0096] Specifically, in order to calculate the surface atomic concentration of magnesium (existence amount PMO, PMX), four peaks (peaks 1 to 4) in the following four peak positions (bond energies) are used for fitting based on the X-ray photoelectron spectroscopy spectrum of Mg kLL (bond energy = 315eV to 298eV). Thus, by calculating the peak area ratio based on peaks 1 and 3, the existence amount PMO of the chemical bond state of magnesium and oxygen is calculated, and by calculating the peak area ratio based on peaks 2 and 4, the existence amount PMX of the chemical bond state of magnesium and the additional element is calculated.

[0097] Peak 1: Bond energy = 303eV ~ 306eV

[0098] Peak 2: Bond energy = Peak position of Peak 1 + 2.48 eV

[0099] Peak 3: Bond energy = Peak position of Peak 2 + 5.38 eV

[0100] Peak 4: Bond energy = Peak position of Peak 3 + 7.03 eV

[0101] In addition, in order to calculate the surface atomic concentration of aluminum (existence amount PAO, PAX), the peak of the X-ray photoelectron spectroscopy spectrum of Al 2s (bond energy = 120eV to 115eV) was fitted and the peak area was quantified. Thus, the existence amount PAO of the chemical bond state of aluminum and oxygen was calculated, and the existence amount PAX of the chemical bond state of aluminum and the additional element was calculated.

[0102] (Other conditions)

[0103] As long as the above-mentioned physical property condition 1 is satisfied, the content CA is not particularly limited. Among them, the content CA is preferably 4500 ppm or more, and more preferably 7800 ppm or less (i.e., 4500 ppm to 7800 ppm). This is because the crystal structure of the positive electrode active material (lithium composite oxide) can be further stabilized, and the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material can be further suppressed.

[0104] In addition, as long as the above-mentioned physical property condition 2 is satisfied, PM and PA are not particularly limited. Among them, PM and PM are preferably 2.9 or more, and PA is 0.4 or less. This is because the crystal structure of the positive electrode active material (lithium composite oxide) can be further stabilized, and the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material can be further suppressed.

[0105] <1-3. Action>

[0106] When the secondary battery is charged, lithium is extracted from the positive electrode 21 in the battery element 20, and the lithium is simultaneously absorbed into the negative electrode 22 via the electrolyte. When the secondary battery is discharged, lithium is extracted from the negative electrode 22 in the battery element 20, and the lithium is simultaneously absorbed into the positive electrode 21 via the electrolyte. During these charge and discharge operations, lithium is absorbed and extracted in an ionic state.

[0107] <1-4. Manufacturing method>

[0108] A positive electrode active material (lithium composite oxide) is produced, and a secondary battery is manufactured using the positive electrode active material.

[0109] [Manufacturing of positive electrode active material]

[0110] First, a positive electrode active material (lithium composite oxide) is produced by the steps described below.

[0111] First, as raw materials, a lithium supply source (lithium compound), a cobalt supply source (cobalt compound), and an aluminum supply source (aluminum compound) are prepared.

[0112] The lithium compound is any one or more of compounds containing lithium as a constituent element, specifically, oxides, carbonates, sulfates, hydroxides, etc. The details of the cobalt compound are the same as the above-mentioned details of the lithium compound, except that cobalt is contained as a constituent element instead of lithium. The details of the aluminum compound are the same as the above-mentioned details of the lithium compound, except that aluminum is contained as a constituent element instead of lithium.

[0113] Here, the lithium compound, the cobalt compound, and the aluminum compound are each in a powdered state. In this case, the average particle size (median particle size D50 (μm)) of each of the lithium compound, the cobalt compound, and the aluminum compound is not particularly limited and can be set arbitrarily.

[0114] Next, a mixture is obtained by mixing the lithium compound, the cobalt compound and the aluminum compound. The mixing ratio (molar ratio of lithium, cobalt and aluminum) of the lithium compound, the cobalt compound and the aluminum compound can be arbitrarily set according to the composition of the positive electrode active material (lithium composite oxide) finally manufactured. In this case, a stirring device such as a high-speed stirrer can also be used to stir the mixture. Conditions such as stirring speed and stirring time can be arbitrarily set.

[0115] Next, after the mixture is calcined, the mixture is slowly cooled. Thus, the lithium compound, the cobalt compound, and the aluminum compound react with each other to obtain a composite oxide containing lithium, cobalt, and aluminum as constituent elements. Conditions such as the calcination temperature and calcination time can be set arbitrarily.

[0116] Next, together with the above-mentioned aluminum compound, a magnesium supply source (magnesium compound) and an additional element supply source (additional compound) are further prepared as other raw materials. The details of the magnesium compound are the same as the details of the above-mentioned lithium compound, except that magnesium is contained instead of lithium as a constituent element. The details of the additional compound are the same as the details of the above-mentioned lithium compound, except that the additional element is contained instead of lithium as a constituent element.

[0117] Here, the magnesium compound and the additional compound are each in a powdered state. In this case, the average particle size (median particle size D50 (μm)) of each of the magnesium compound and the additional compound is not particularly limited and can be arbitrarily set.

[0118] Next, a precursor is prepared by mixing the composite oxide, the aluminum compound, the magnesium compound and the additional compound. The mixing ratio of the composite oxide, the aluminum compound, the magnesium compound and the additional compound (the molar ratio of lithium, cobalt, aluminum, magnesium and the additional element) can be arbitrarily set according to the composition of the positive electrode active material (lithium composite oxide) finally manufactured. In this case, the precursor can also be stirred in the same manner as in the case of stirring the above-mentioned mixture.

[0119] Finally, the precursor is fired under an oxygen flow. Thus, the precursor, the aluminum compound, the magnesium compound, and the additional compound react with each other to synthesize a lithium composite oxide containing lithium, cobalt, aluminum, magnesium, and the additional element as constituent elements. Thus, a positive electrode active material (lithium composite oxide) can be obtained. Conditions such as the firing temperature and firing time can be set arbitrarily.

[0120] [Manufacturing of Secondary Batteries]

[0121] Next, a secondary battery is produced using the above-mentioned positive electrode active material (lithium composite oxide) through the steps described below.

[0122] (Production of positive electrode)

[0123] By mixing the positive electrode active material, the positive electrode binder and the positive electrode conductive agent with each other, a positive electrode mixture is prepared, and then the positive electrode mixture is put into an organic solvent, etc., thereby preparing a paste-like positive electrode mixture slurry. Thereafter, the positive electrode mixture slurry is applied to both sides of the positive electrode collector 21A to form a positive electrode active material layer 21B. It should be noted that the positive electrode active material layer 21B can also be compression molded using a roller press or the like. In this case, the positive electrode active material layer 21B can be heated, and compression molding can also be repeated multiple times. Thus, the positive electrode 21 is made.

[0124] (Production of negative electrode)

[0125] The negative electrode 22 is made by the same steps as the steps for making the positive electrode 21 described above. Specifically, a negative electrode mixture is made by mixing a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent, and then the negative electrode mixture is put into an organic solvent, etc., thereby preparing a paste-like negative electrode mixture slurry. Thereafter, the negative electrode mixture slurry is applied to both sides of the negative electrode collector 22A, thereby forming a negative electrode active material layer 22B. Of course, the negative electrode active material layer 22B can also be compression molded. Thus, the negative electrode 22 is made.

[0126] (Preparation of Electrolyte)

[0127] The electrolyte salt is added to the solvent so that the electrolyte salt is dispersed or dissolved in the solvent, thereby preparing an electrolytic solution.

[0128] (Assembly of secondary batteries)

[0129] First, the positive electrode lead 31 is connected to the positive electrode 21 (positive electrode collector 21A) by welding or the like, and at the same time, the negative electrode lead 32 is connected to the negative electrode 22 (negative electrode collector 22A) by welding or the like.

[0130] Next, the positive electrode 21 and the negative electrode 22 are stacked on each other with the separator 23 interposed therebetween, and then the positive electrode 21, the negative electrode 22, and the separator 23 are wound to produce a wound body. The wound body has the same structure as the battery element 20 except that the electrolyte is not impregnated in each of the positive electrode 21, the negative electrode 22, and the separator 23. Next, the wound body is pressed using a press machine or the like to be formed into a flat shape.

[0131] Next, the roll is accommodated in the recessed portion 10U, and then the outer packaging films 10 are folded so that the outer packaging films 10 face each other with the roll interposed therebetween. Next, the outer peripheral edges of the two sides of the outer packaging films 10 (welding layers) facing each other are welded to each other by using a heat welding method or the like, thereby housing the roll in the bag-shaped outer packaging film 10.

[0132] Finally, the electrolyte is injected into the bag-shaped outer packaging film 10, and then the outer peripheral edge of the remaining side of the outer packaging film 10 (welding layer) is welded to each other using a heat welding method or the like. In this case, the sealing film 41 is inserted between the outer packaging film 10 and the positive electrode lead 31, and the sealing film 42 is inserted between the outer packaging film 10 and the negative electrode lead 32. Thus, the electrolyte is impregnated in the winding body, and the battery element 20 as a wound electrode body is manufactured, and the battery element 20 is sealed in the bag-shaped outer packaging film 10 to assemble into a secondary battery.

[0133] (Stabilization of secondary batteries)

[0134] The assembled secondary battery is charged and discharged. The ambient temperature, the number of charge and discharge cycles, and the charge and discharge conditions can be set arbitrarily. Thus, a coating is formed on the surface of the negative electrode 22, etc., so that the state of the secondary battery is electrochemically stabilized.

[0135] Thus, a secondary battery using the outer film 10, that is, a laminated film type secondary battery is completed.

[0136] <1-5. Functions and effects>

[0137] According to the secondary battery, the positive electrode active material (layered rock salt type lithium composite oxide) of the positive electrode 21 contains lithium, cobalt, aluminum, magnesium, additional elements and oxygen as constituent elements. In addition, the analysis results (contents CA, CM) of the positive electrode active material using ICP emission spectrometry satisfy physical property condition 1, and the surface analysis results (and PA, PM) of the positive electrode active material using XPS satisfy physical property condition 2.

[0138] In this case, first, the lithium composite oxide contains aluminum as a constituent element. 3+ ) is arranged at the position of cobalt in the crystal structure of the lithium composite oxide. Thus, the crystal structure of the positive electrode active material is stabilized.

[0139] Second, the lithium composite oxide contains magnesium as a constituent element, and magnesium ions (Mg 2+ ) has an ion radius close to that of a lithium ion. Thus, when lithium is extracted from the lithium composite oxide, magnesium is arranged at the position of lithium in the crystal structure of the lithium composite oxide, thereby stabilizing the crystal structure of the positive electrode active material during charging.

[0140] Third, the lithium composite oxide contains an additional element as a constituent element, and the additional element reduces the reactivity of the lithium composite oxide with respect to the electrolyte, thereby suppressing the reaction between the positive electrode active material and the electrolyte on the surface of the positive electrode active material.

[0141] Fourth, the analysis results of the positive electrode active material using ICP emission spectrometry satisfy physical property condition 1, so the lithium composite oxide as a whole contains a sufficient amount of aluminum as a constituent element. Therefore, as described above, in the crystal structure of the lithium composite oxide, aluminum is easily arranged at the position of cobalt, so the crystal structure of the positive electrode active material is more stabilized.

[0142] Fifth, regarding the analysis results of the surface of the positive electrode active material using XPS, since physical property condition 2 is satisfied, magnesium is concentrated near the surface of the lithium composite oxide. 2+ ) has an ionic radius close to that of lithium ions, so magnesium is easily arranged at the position of lithium in the crystal structure of the lithium composite oxide. Therefore, when the positive electrode active material is manufactured (when the precursor is fired), even if lithium is missing near the surface, magnesium is more likely to be present preferentially near the surface than aluminum. Moreover, when the positive electrode active material is manufactured (when the precursor is fired), magnesium is fired together with the additional element, so magnesium is easily concentrated near the surface of the lithium composite oxide, and magnesium concentrated near the surface of the lithium composite oxide is easy to react with the additional element, so it becomes easy for a chemical bond (Mg-X) between magnesium and the additional element to exist near the surface of the lithium composite oxide.

[0143] As a result, during charging, the crystal structure of the positive electrode active material (lithium composite oxide) is stabilized and the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material is suppressed, thereby achieving excellent initial capacity characteristics, cycle characteristics and storage characteristics.

[0144] In particular, in the lithium composite oxide, when the molar ratio of cobalt is larger than the molar ratios of aluminum, magnesium, and the additional element, the energy density is improved, and thus a higher effect can be obtained.

[0145] In addition, if the aluminum content CA is 4500 ppm or more, preferably 7800 ppm or less, the crystal structure of the positive electrode active material (lithium composite oxide) is further stabilized, and the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material is further suppressed, thereby achieving a higher effect.

[0146] In addition, if PM is 2.9 or more and PA is 0.4 or less, the crystal structure of the positive electrode active material (lithium composite oxide) is further stabilized and the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material is further suppressed, thereby achieving a higher effect.

[0147] Furthermore, if the secondary battery is a lithium ion secondary battery, a sufficient battery capacity can be stably obtained by utilizing insertion and extraction of lithium, and thus a higher effect can be obtained.

[0148] In addition, according to the positive electrode active material, a layered rock salt type lithium composite oxide having the above-mentioned composition is included, and the analysis results using ICP emission spectroscopy and XPS satisfy physical property conditions 1 and 2. Therefore, for the same reasons as those for the above-mentioned secondary battery, in a secondary battery using the positive electrode active material, excellent initial capacity characteristics, cycle characteristics, and storage characteristics can be obtained.

[0149] In addition, according to the positive electrode 21, the positive electrode active material includes a layered rock salt type lithium composite oxide having the above-mentioned composition, and the analysis results of the positive electrode active material using ICP emission spectroscopy and XPS satisfy physical property conditions 1 and 2. Therefore, for the same reasons as those for the above-mentioned secondary battery, in the secondary battery using the positive electrode 21, excellent initial capacity characteristics, cycle characteristics, and storage characteristics can be obtained.

[0150] <2. Modifications>

[0151] Next, a modification of the above-mentioned secondary battery will be described. As described below, the structure of the secondary battery can be appropriately changed. In addition, any two or more of the series of modifications described below can also be combined with each other.

[0152] [Modification 1]

[0153] The separator 23 which is a porous film is used. However, although not specifically shown here, a laminated separator including a polymer compound layer may be used instead of the separator 23 which is a porous film.

[0154] Specifically, the laminated diaphragm includes a porous film with a pair of faces and a polymer compound layer disposed on one or both sides of the porous film. This is because, since the diaphragm is relatively close to the positive electrode 21 and the negative electrode 22, the positional offset of the battery element 20 (the winding offset of the positive electrode 21, the negative electrode 22 and the diaphragm) is not easy to occur. Thus, even if the decomposition reaction of the electrolyte occurs, the secondary battery is not easy to expand. The polymer compound layer includes polymer compounds such as polyvinylidene fluoride. This is because polyvinylidene fluoride, etc. have excellent physical strength and electrochemical stability.

[0155] It should be noted that one or both of the porous membrane and the polymer compound layer may contain multiple insulating particles. This is because multiple insulating particles dissipate heat when the secondary battery is heated, so the safety (heat resistance) of the secondary battery is improved. The insulating particles include any one or more of inorganic particles and resin particles. Specific examples of inorganic particles are particles of aluminum oxide, aluminum nitride, boehmite, silicon oxide, titanium oxide, magnesium oxide and zirconium oxide. Specific examples of resin particles are particles such as acrylic resin and styrene resin.

[0156] When a laminated separator is produced, a precursor solution containing a polymer compound and an organic solvent is prepared, and then the precursor solution is applied to one or both surfaces of a porous membrane. In this case, a plurality of insulating particles may be added to the precursor solution as needed.

[0157] When the laminated separator is used, lithium ions can also move between the positive electrode 21 and the negative electrode 22 , so the same effect can be obtained.

[0158] [Modification 2]

[0159] A liquid electrolyte, namely, an electrolytic solution is used. However, although not specifically shown here, an electrolyte layer which is a gel electrolyte may be used instead of the electrolytic solution.

[0160] In the battery element 20 using the electrolyte layer, the positive electrode 21 and the negative electrode 22 are stacked on each other with the separator 23 and the electrolyte layer interposed therebetween, and the positive electrode 21, the negative electrode 22, the separator 23 and the electrolyte layer are wound. The electrolyte layer is interposed between the positive electrode 21 and the separator 23, and between the negative electrode 22 and the separator 23.

[0161] Specifically, the electrolyte layer includes an electrolyte and a polymer compound, and in the electrolyte layer, the electrolyte is maintained by the polymer compound. This is because leakage of the electrolyte can be prevented. The structure of the electrolyte is as described above. The polymer compound includes polyvinylidene fluoride, etc. When forming the electrolyte layer, after preparing a precursor solution including an electrolyte, a polymer compound, and an organic solvent, the precursor solution is coated on one or both sides of each of the positive electrode 21 and the negative electrode 22.

[0162] Even when such an electrolyte layer is used, lithium ions can move between the positive electrode 21 and the negative electrode 22 via the electrolyte layer, so the same effect can be obtained.

[0163] <3. Applications of secondary batteries>

[0164] Next, uses (application examples) of the above-mentioned secondary battery will be described.

[0165] The use of secondary batteries is not particularly limited. Secondary batteries used as power sources can be the main power source of electronic equipment and electric vehicles, etc., or they can be auxiliary power sources. The main power source is the power source that is used first, regardless of the presence or absence of other power sources. The auxiliary power source is a power source that is used instead of the main power source, or a power source that is switched from the main power source.

[0166] Specific examples of the uses of secondary batteries are as follows. Electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, stereo headphones, portable radios, and portable information terminals (including portable electronic devices). Storage devices such as backup power supplies and memory cards. Power tools such as electric drills and electric saws. Battery packs mounted on electronic devices, etc. Medical electronic devices such as pacemakers and hearing aids. Electric vehicles such as electric vehicles (including hybrid vehicles). Power storage systems such as household or industrial battery systems that store electricity in advance in preparation for emergencies, etc. In these uses, one secondary battery or multiple secondary batteries can be used.

[0167] The battery pack may use a single cell or a battery pack. An electric vehicle is a vehicle that uses a secondary battery as a driving power source to operate (drive). As mentioned above, it may also be a hybrid vehicle that has a driving source other than a secondary battery. In a home power storage system, the power stored in the secondary battery as a power storage source can be used to use home electrical products, etc.

[0168] Here, an example of application of the secondary battery will be described in detail. The configuration of the application example described below is just an example and can be modified as appropriate.

[0169] Figure 3: represents the frame structure of the battery pack. The battery pack described here is a battery pack using one secondary battery (so-called soft pack), and is installed in electronic devices such as smartphones.

[0170] like Figure 3 As shown, the battery pack includes a power source 51 and a circuit board 52. The circuit board 52 is connected to the power source 51 and includes a positive electrode terminal 53, a negative electrode terminal 54, and a temperature detection terminal 55.

[0171] The power source 51 includes a secondary battery. In the secondary battery, the positive lead is connected to the positive terminal 53, and the negative lead is connected to the negative terminal 54. Since the power source 51 can be connected to the outside through the positive terminal 53 and the negative terminal 54, it can be charged and discharged. The circuit substrate 52 includes a control unit 56, a switch 57, a thermistor element (PTC) element 58, and a temperature detection unit 59. In addition, the PTC element 58 can also be omitted.

[0172] The control unit 56 includes a central processing unit (CPU) and a memory, etc., and controls the operation of the entire battery pack. The control unit 56 detects and controls the use state of the power source 51 as needed.

[0173] It should be noted that when the voltage of the power source 51 (secondary battery) reaches the overcharge detection voltage or the overdischarge detection voltage, the control unit 56 cuts off the switch 57 so that the charging current does not flow through the current path of the power source 51. The overcharge detection voltage and the overdischarge detection voltage are not particularly limited. For example, the overcharge detection voltage is 4.2V±0.05V, and the overdischarge detection voltage is 2.4V±0.1V.

[0174] The switch 57 includes a charge control switch, a discharge control switch, a charge diode, and a discharge diode, and switches the connection between the power supply 51 and the external device according to the instruction of the control unit 56. The switch 57 includes a field effect transistor (MOSFET) using a metal oxide semiconductor, and detects the charge and discharge current based on the on-resistance of the switch 57.

[0175] The temperature detection unit 59 includes a temperature detection element such as a thermistor, and uses the temperature detection terminal 55 to measure the temperature of the power supply 51, and outputs the temperature measurement result to the control unit 56. The temperature measurement result measured by the temperature detection unit 59 is used when the control unit 56 performs charge and discharge control when abnormal heating occurs, and when the control unit 56 performs correction processing when calculating the remaining capacity.

[0176] Example

[0177] Examples of the present technology will be described.

[0178] (Examples 1 to 10 and Comparative Examples 11 to 16)

[0179] As described below, a positive electrode active material was manufactured, and a secondary battery for testing was manufactured using the positive electrode active material, and then the performance of the secondary battery was evaluated. It should be noted that in each of Tables 1 and 2 described later, in order to simplify the description, Examples 1 to 10 are described as "Examples 1 to 10", and Comparative Examples 11 to 16 are described as "Comparative Examples 11 to 16".

[0180] Figure 4 The cross-sectional structure of the secondary battery used for the test is shown. This secondary battery is a coin-type secondary battery using two metal outer packaging members (outer packaging can 102 and outer packaging cup 104) that can fit together.

[0181] In a coin-type secondary battery, such as Figure 4 As shown, the test electrode 101 is accommodated in the outer packaging cup 104, and the counter electrode 103 is accommodated in the outer packaging can 102. The test electrode 101 and the counter electrode 103 are stacked on each other via a separator 105, and the outer packaging can 102 and the outer packaging cup 104 are riveted to each other via a gasket 106. The electrolyte is impregnated in the test electrode 101, the counter electrode 103, and the separator 105, respectively.

[0182] [Manufacturing of positive electrode active material]

[0183] The positive electrode active material (lithium composite oxide) was produced by the steps described below.

[0184] First, as raw materials, powdered lithium compounds (lithium carbonate (Li2CO3)), powdered cobalt compounds (cobalt oxide (CoO2)) and powdered aluminum compounds (aluminum oxide (Al2O3)) were prepared. The average particle size (median particle size D50 (μm)) of the aluminum compound is shown in Table 1.

[0185] In addition, in Table 1, the lithium compound, the cobalt compound, and the aluminum compound are expressed as "Li compound", "Co compound", and "Al compound", respectively.

[0186] Next, a mixture is obtained by mixing a lithium compound, a cobalt compound and an aluminum compound. In this case, the mixing ratio of the lithium compound, the cobalt compound and the aluminum compound (the molar ratio of lithium, cobalt and aluminum) is 1.02:0.99:0.01. In addition, the mixing ratio of the cobalt compound is changed according to the mixing ratio of the aluminum compound, as shown in Table 1, so that the mixing ratio of the aluminum compound is changed. Next, the mixture is stirred using a high-speed stirrer. The stirring time (hours) is shown in Table 1.

[0187] Next, the mixture was calcined in air (calcination temperature = 1050°C, calcination time = 8 hours), and then slowly cooled. Thus, a powdery composite oxide containing lithium, cobalt, and aluminum as constituent elements (lithium cobalt oxide containing aluminum, average particle size (median particle size D50) = 20 μm, specific surface area = 0.3 m 2 / g).

[0188] Next, together with the above-mentioned powdered aluminum compound (aluminum oxide), a powdered magnesium compound (magnesium oxide (MgO2)) and two powdered additional compounds were further prepared as other raw materials. As the two additional compounds, lithium fluoride (LiF) and magnesium fluoride (MgF2) whose additional element is fluorine, lithium phosphate (Li3PO4) and magnesium phosphate (Mg3(PO4)2) whose additional element is phosphorus, and lithium sulfide (Li2S) and magnesium sulfide (MgS) whose additional element is sulfur were used. Hereinafter, of the above-mentioned two additional compounds, the former additional compound is referred to as the "first additional compound", and the latter additional compound is referred to as the "second additional compound".

[0189] In addition, in Table 1, the magnesium compound is expressed as "Mg compound".

[0190] Next, for the composite oxide, a mixture was obtained by mixing 500 ppm of an aluminum compound, 500 ppm of a magnesium compound, 500 ppm of a first additional compound, and 250 ppm of a second additional compound. In this case, the mixing amount (ppm) of the aluminum compound and the mixing amount (ppm) of the magnesium compound were changed as shown in Table 1.

[0191] Finally, the mixture was calcined under an oxygen flow (calcination temperature = 800° C., calcination time = 5 hours). Thus, a powdery composite oxide (lithium composite oxide) containing lithium, cobalt, aluminum, magnesium and additional elements as constituent elements was synthesized to obtain a positive electrode active material (lithium composite oxide).

[0192] For comparison, a positive electrode active material was produced by the same procedure except that the additional compound was not used, thereby producing a positive electrode active material that did not contain the additional element as a constituent element.

[0193] [Manufacturing of Secondary Batteries]

[0194] A secondary battery (lithium ion secondary battery) was manufactured using the above-mentioned positive electrode active material through the steps described below.

[0195] (Production of test pole)

[0196] First, 98 parts by mass of a positive electrode active material (lithium composite oxide), 1.2 parts by mass of a positive electrode binder (polyvinylidene fluoride), and 0.8 parts by mass of a positive electrode conductor (ketjen black as an amorphous carbon powder) are mixed together to prepare a positive electrode mixture. Next, the positive electrode mixture is put into an organic solvent (N-methyl-2-pyrrolidone), and then the organic solvent is stirred to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of a positive electrode collector (aluminum foil with a thickness of 12 μm) using a coating device, and then the positive electrode mixture slurry is hot-air dried to form a positive electrode active material layer. Finally, after the positive electrode active material layer is compression-molded using a roller press, the positive electrode collector formed with the positive electrode active material layer is punched into a disc shape (diameter = 15 mm). Thus, a test pole 101 (positive electrode) is produced.

[0197] (Fabrication of Counter Electrode)

[0198] First, 95 parts by mass of a negative electrode active material (graphite) and 5 parts by mass of a negative electrode binder (polyvinylidene fluoride) are mixed with each other to form a negative electrode mixture. Next, the negative electrode mixture is put into an organic solvent (N-methyl-2-pyrrolidone), and then the organic solvent is stirred to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of the negative electrode collector (copper foil with a thickness of 12 μm) using a coating device, and then the negative electrode mixture slurry is hot-air dried to form a negative electrode active material layer. Finally, after the negative electrode active material layer is compression-molded using a roller press, the negative electrode collector formed with the negative electrode active material layer is punched into a disc shape (diameter = 16 mm). Thus, a counter electrode 103 (negative electrode) is produced.

[0199] (Preparation of Electrolyte)

[0200] An electrolyte salt (lithium hexafluorophosphate (LiPF6) as a lithium salt) is put into a solvent (ethylene carbonate and propylene carbonate as carbonate compounds), and then the solvent is stirred. In this case, the mixing ratio (weight ratio) of ethylene carbonate and propylene carbonate is 50:50, and the content of the electrolyte salt relative to the solvent is 1 mol / kg. Thus, the electrolyte salt is dispersed or dissolved in the solvent, thereby preparing an electrolytic solution.

[0201] (Assembly of secondary batteries)

[0202] First, the test electrode 101 is housed inside the outer cup 104, and the counter electrode 103 is housed inside the outer can 102. Next, the test electrode 101 housed inside the outer cup 104 and the counter electrode 103 housed inside the outer can 102 are stacked on each other via a separator 105 (a porous polyolefin film with a thickness of 25 μm) impregnated with an electrolyte. Thus, a portion of the electrolyte impregnated in the separator 105 is impregnated into the test electrode 101 and the counter electrode 103, respectively. Finally, in a state where the test electrode 101 and the counter electrode 103 are stacked on each other via the separator 105, the outer can 102 and the outer cup 104 are riveted to each other via the gasket 106. Thus, the test electrode 101, the counter electrode 103, the separator 105, and the electrolyte are sealed by the outer can 102 and the outer cup 104, and a coin-type secondary battery is assembled.

[0203] (Stabilization of secondary batteries)

[0204] The assembled secondary battery is charged and discharged for one cycle at room temperature (temperature = 23°C). When charging, constant current charging is performed at a current of 0.1C until the voltage reaches 4.2V, and then constant voltage charging is performed at the voltage of 4.2V until the current reaches 0.05C. When discharging, constant current discharge is performed at a current of 0.1C until the voltage reaches 3.0V. 0.1C refers to the current value that completely discharges the battery capacity (theoretical capacity) within 10 hours, and 0.05C refers to the current value that completely discharges the battery capacity within 20 hours.

[0205] Thus, since a coating film is formed on the surface of each of the test electrode 101 and the counter electrode 103, the state of the secondary battery is electrochemically stabilized. Thus, a coin-type secondary battery is completed.

[0206] It should be noted that after the secondary battery was completed, the positive electrode active material was analyzed by ICP emission spectrometry to measure the aluminum content CA (ppm) and the magnesium content CM (ppm), respectively. The results shown in Table 2 were obtained.

[0207] In addition, by analyzing the surface of the positive electrode active material using XPS, the amounts of PAO, PAX, PMO, and PMX were measured, and PA and PM were calculated, respectively. The results shown in Table 2 were obtained.

[0208] It should be noted that in Table 2, the magnitude relationship between the contents CA and CM is shown, and the magnitude relationship between the contents PA and PM is also shown. Regarding the magnitude relationship between the contents CA and CM, "large" means that the content CA is greater than the content CM, and "small" means that the content CA is less than the content CM. In addition, regarding the magnitude relationship between the contents PA and PM, "large" means that the content PM is greater than the content PA, and "small" means that the content PM is less than the content PA.

[0209] [Performance Evaluation]

[0210] The performance of the secondary battery (initial capacity characteristics, cycle characteristics, and storage characteristics) was evaluated, and the results shown in Table 2 were obtained.

[0211] (Initial Capacity Characteristics)

[0212] The discharge capacity (initial capacity (mAh)) was measured by charging and discharging the secondary battery for one cycle in a high temperature environment (temperature = 45°C). During charging, constant current charging was performed at a current of 10 mA until the voltage reached 4.45 V, and then constant voltage charging was performed at the voltage of 4.45 V until the total charging time reached 2.5 hours. During discharging, constant current discharge was performed at a current of 9 mA until the voltage reached 3.0 V.

[0213] (Cycle Characteristics)

[0214] Through the above steps, the initial capacity was measured in a high temperature environment (temperature = 45°C), and then the secondary battery was repeatedly charged and discharged in the same environment until the total number of cycles reached 500 cycles, thereby measuring the discharge capacity (discharge capacity of the 500th cycle). The charge and discharge conditions after the second cycle are the same as those of the first cycle. Thus, the capacity retention rate (%) is calculated = (discharge capacity of the 500th cycle / initial capacity) × 100.

[0215] (Save Properties)

[0216] First, the secondary battery was charged, and then the charged secondary battery was stored in a high temperature environment (temperature = 60°C) (storage time = 14 days). The charging conditions were the same as those when investigating the initial capacity characteristics. Next, the stored secondary battery was disassembled, and the counter electrode 103 (negative electrode) was recovered. Next, in 15 ml (= 15 cm 3 The counter electrode 103 was boiled in hydrochloric acid (concentration = 1 mol / kg) (boiling time = 15 minutes), and then the hydrochloric acid was filtered to obtain a sample (solution) for analysis. Next, the sample was analyzed by using ICP emission spectrometry to measure the concentration of cobalt contained in the sample. Finally, the amount of cobalt dissolved was calculated based on the calculation formula: the amount of cobalt dissolved = the concentration of cobalt / the weight of the positive electrode active material.

[0217] In addition, the values ​​of the elution amount shown in Table 2 show the values ​​normalized with the value of the elution amount in Example 5 being 100.

[0218] [Table 1]

[0219]

[0220] [Table 2] Lithium composite oxide (constituent elements = Li, Co, Al, Mg, X (F, P or S), O)

[0221]

[0222] [Investigation]

[0223] As shown in Table 2, the initial capacity characteristics, cycle characteristics, and storage characteristics vary greatly depending on the physical properties of the positive electrode active material (lithium composite oxide).

[0224] Specifically, when both physical property condition 1 (content CA> content CM) of the analysis result of ICP emission spectrometry and physical property condition 2 (and PM> and PA) of the analysis result of XPS are satisfied (Examples 1 to 10), compared with the case where both physical property conditions 1 and 2 are not satisfied (Comparative Examples 11 to 16), the capacity retention rate is increased while ensuring the initial capacity, and the dissolution amount is reduced. That is, since the decomposition reaction of the electrolyte caused by the reactivity of the positive electrode active material (lithium composite oxide) is suppressed, the capacity retention rate is increased while ensuring the initial capacity, and since the crystal structure of the positive electrode active material is stabilized, the dissolution amount of cobalt is reduced.

[0225] In particular, when both physical property conditions 1 and 2 are met, a series of tendencies described below are obtained. First, when the molar ratio of cobalt in the positive electrode active material (lithium composite oxide) is greater than the molar ratios of aluminum, magnesium and the additional elements, a sufficient initial capacity is obtained. Second, when the content CA is above 4500ppm, while ensuring the initial capacity, the capacity retention rate is further increased, and the dissolution amount is further reduced. In this case, when the content CA is below 7800ppm, while obtaining a high capacity retention rate and fully suppressing the dissolution amount, a higher initial capacity is obtained. Third, when PM is above 2.9 and PA is below 0.4, while ensuring the initial capacity, the capacity retention rate is further increased and the dissolution amount is further reduced. Fourth, when additional elements are used, independent of the type of the additional element (fluorine, phosphorus or sulfur), the common advantages of increasing the capacity retention rate while ensuring the initial capacity and reducing the dissolution amount are obtained.

[0226] [Summarize]

[0227] According to the results shown in Table 2, when the positive electrode active material (lithium composite oxide of layered rock salt type) contains lithium, cobalt, aluminum, magnesium, additional elements and oxygen as constituent elements, and satisfies the physical property condition 1 of the analysis result using ICP emission spectrometry and the physical property condition 2 of the analysis result using X-ray photoelectron spectroscopy at the same time, while ensuring the initial capacity, the capacity retention rate increases, and the dissolution amount decreases. Thus, in the secondary battery, excellent initial capacity characteristics, cycle characteristics and storage characteristics are obtained.

[0228] Although the present technology has been described above by taking one embodiment and one example, the structure of the present technology is not limited to the structure described in one embodiment and one example, and various modifications are possible.

[0229] Specifically, although the battery structure of the secondary battery is described as a laminated film type and a coin type, the battery structure is not particularly limited and may be other battery structures such as a cylindrical type, a square type, and a button type.

[0230] In addition, although the case where the element structure of the battery element is a winding type is described, the element structure of the battery element is not particularly limited. The element structure may adopt other battery structures such as a stacked type in which electrodes (positive electrodes and negative electrodes) are stacked, and a repeatedly folded type in which electrodes (positive electrodes and negative electrodes) are folded into a Z shape.

[0231] In addition, although the case where the electrode reaction material is lithium is described, the electrode reaction material is not particularly limited. Specifically, as described above, the electrode reaction material can be other alkali metals such as sodium and potassium, or alkaline earth metals such as beryllium, magnesium and calcium. In addition, the electrode reaction material can also be other light metals such as aluminum.

[0232] It should be noted that the above-mentioned positive electrode active material and positive electrode are not limited to secondary batteries, but can also be applied to other electrochemical devices such as capacitors.

[0233] The effects described in this specification are merely examples, and therefore the effects of the present technology are not limited to the effects described in this specification. Therefore, the present technology can also achieve other effects.

Claims

1. A secondary battery, The secondary battery comprises a positive electrode including a positive electrode active material, a negative electrode, and an electrolyte. The positive electrode active material includes a layered rock salt type lithium composite oxide, The lithium composite oxide contains lithium, cobalt, aluminum, magnesium, an additional element, and oxygen as constituent elements, and the additional element contains at least one of fluorine, phosphorus, and sulfur. When the positive electrode active material is analyzed by inductively coupled plasma emission spectrometry, the content of aluminum is greater than the content of magnesium, and at the same time, When the surface of the positive electrode active material is analyzed using X-ray photoelectron spectroscopy, the sum of the amount of the chemical bond state of the magnesium and the oxygen and the amount of the chemical bond state of the magnesium and the additional element is greater than the sum of the amount of the chemical bond state of the aluminum and the oxygen and the amount of the chemical bond state of the aluminum and the additional element.

2. The secondary battery according to claim 1, wherein The molar ratio of the cobalt is greater than the molar ratios of the aluminum, the magnesium, and the additional element.

3. The secondary battery according to claim 1 or 2, wherein: The aluminum content is greater than 4500 ppm.

4. The secondary battery according to claim 3, wherein The aluminum content is 7800 ppm or less.

5. The secondary battery according to any one of claims 1 to 4, wherein The sum of the amount of the chemically bonded state of the magnesium and the oxygen and the amount of the chemically bonded state of the magnesium and the additional element is 2.9 or more, and The sum of the amount of the aluminum and the oxygen in a chemically bonded state and the amount of the aluminum and the additional element in a chemically bonded state is 0.4 or less.

6. The secondary battery according to any one of claims 1 to 5, wherein The secondary battery is a lithium ion secondary battery.

7. A positive electrode active material for a secondary battery, The positive electrode active material for a secondary battery includes a layered rock salt type lithium composite oxide. The lithium composite oxide contains lithium, cobalt, aluminum, magnesium, an additional element, and oxygen as constituent elements, and the additional element contains at least one of fluorine, phosphorus, and sulfur. When the positive electrode active material is analyzed by inductively coupled plasma emission spectrometry, the content of aluminum is greater than the content of magnesium, and at the same time, When the surface is analyzed using X-ray photoelectron spectroscopy, the sum of the amount of the chemical bond state of the magnesium and the oxygen and the amount of the chemical bond state of the magnesium and the additional element is greater than the sum of the amount of the chemical bond state of the aluminum and the oxygen and the amount of the chemical bond state of the aluminum and the additional element.

8. A positive electrode for a secondary battery, The positive electrode for a secondary battery comprises a positive electrode active material. The positive electrode active material includes a layered rock salt type lithium composite oxide, The lithium composite oxide contains lithium, cobalt, aluminum, magnesium, an additional element, and oxygen as constituent elements, and the additional element contains at least one of fluorine, phosphorus, and sulfur. When the positive electrode active material is analyzed by inductively coupled plasma emission spectrometry, the content of aluminum is greater than the content of magnesium, and at the same time, When the surface of the positive electrode active material is analyzed using X-ray photoelectron spectroscopy, the sum of the amount of the chemical bond state of the magnesium and the oxygen and the amount of the chemical bond state of the magnesium and the additional element is greater than the sum of the amount of the chemical bond state of the aluminum and the oxygen and the amount of the chemical bond state of the aluminum and the additional element.

Citation Information

Patent Citations

  • Manufacturing method of lithium compound oxide for lithium secondary battery cathode

    JP2005347211A

  • compact handheld device

    JP2016507343A

  • Positive electrode active material particle, and method of manufacturing the same

    JP2018190700A

  • Lithium ion secondary battery

    CN101199065A

  • Lithium nickel-manganese-cobalt oxide cathode powders for high voltage lithium-ion batteries

    CN107210422A